The effect of honeycomb and rectangular structures made with PLA 3D printing on the impact strength of sandwich composite - Setiawan, Ferry; Sofyan, Rifal Ma'rifatulloh; Putra, Ikbal Rizky (Jurnal Polimesin, 2025)
Composites with a sandwich structure with a core using polymer materials has been widely applied, 3D printing technology makes polymer structures with various geometric variations, but research on the influence of geometric shapes made with 3D printing machines with PLA materials bonded using a one-step manufacturing process with a hand lay up method is still not widely done. The purpose of this study is to determine the comparison of the impact strength of sandwich composite materials with core honeycomb and rectangular made from PLA 3D printing made with a one-step process manufacturing system with the hand layup method. The sandwich composite composition used is fiberglass as the face skin and the matrix uses epoxy resin, where this resin also functions as an adhesive. The absorption energy data obtained with the best value was a honeycomb core specimen with an average value of 3.2758 Joules compared to the absorption energy data from the rectangular core which had an average value of 3.1552 Joules. The impact price data obtained with the best value was the honeycomb core with an average value of 0.0225 J/mm2, when compared to the impact price data from the rectangular core which had an average value of 0.0217 J/mm2. From this study, it can be concluded that sandwich composites with honeycomb cores have better impact strength property values because they have a more compact arrangement of materials that are bonded to each other on 6 sides, and also because honeycomb structures have a higher weight of 20 grams compared to rectangular structures that weigh 18.